A Comprehensive Review of Fingerprint Development : Exploring Unconventional Powder-Based Techniques - Ghodake, Komal; Smitesh S. Nalage (International Journal of Scientific Research in Science and Technology, 2024)
Fingerprint development remains a crucial aspect of forensic science, aiding in the identification and resolution of criminal cases. This review paper systematically explores the efficacy and potential of various unconventional and natural substances in fingerprint development. Focusing on an array of substances such as turmeric powder, Fuller's clay powder (Multani Mitti), food color, Holi color, durian seeds powder, soil powder, talcum powder, traditional powders, pooja materials, corn seed powder, silica gel G, broccoli powder, medicine powder, salt, sugar powder, and brick powder, this paper discusses their applicability, advantages, limitations, and comparative effectiveness in developing latent fingerprints. The review encompasses studies and experiments conducted to assess the suitability of these substances for fingerprint development across different surfaces and environmental conditions. Additionally, this article examines the environmental and cost-effective benefits of using natural and non-conventional materials in forensic investigations and their sustainability and availability compared to traditional chemical reagents.
Keywords: Powder method; Fingerprint; Forensic Science; Fingerprint development